Advanced flow visualization with HiVision - Bönisch, Sebastian; Heuveline, Vincent (Reactive flows, diffusion and transport, 2007)
The features and the design concept of the visualization software HiVision are presented. The platform HiVision which was primarily developed for the exploration of data in the area of Computational Fluid Dynamics (CFD), is being used nowadays in numerous applications related to numerical simulation. The main strength of the HiVision package lies in its object-oriented design and in the integration of several powerful external toolkits (VTK,Qt,MPI). The features of HiVision are demonstrated by means of selected examples.